2014
DOI: 10.3906/sag-1209-30
|View full text |Cite
|
Sign up to set email alerts
|

Expression of NADPH-d in the vagal nuclei of the chronic esophagitis model in rats

Abstract: Agricultural biomass is the world's largest, most sustainable, and most promising renewable energy source. This study investigated the potential of Karanja (Pongamia pinnata) oilseed residual waste (defatted kernel, hull, and their mixture) as a source of ethanol. The pretreatment of the finely ground samples was carried out using dilute sulfuric acid (0.5%) hydrolysis at a higher temperature of 121 °C and 15 psi pressure for 90 min. The pretreatment usually removes the lignin and facilitates the hydrolysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
2
0
1
Order By: Relevance
“…Previous experiments by our group have shown that c-fos expression significantly increased in the NTS/DMV and AP in rats receiving an acid plus pepsin perfusion [10]. The proposed mechanism was that exposure of the lower part of the esophagus to acid-pepsin stimulated the mucosal receptors, which in turn activated the neurons of the NTS and then of the DMV to modulate esophageal peristalsis [11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous experiments by our group have shown that c-fos expression significantly increased in the NTS/DMV and AP in rats receiving an acid plus pepsin perfusion [10]. The proposed mechanism was that exposure of the lower part of the esophagus to acid-pepsin stimulated the mucosal receptors, which in turn activated the neurons of the NTS and then of the DMV to modulate esophageal peristalsis [11].…”
Section: Introductionmentioning
confidence: 99%
“…In rats, nitric oxide synthase (NOS)-containing abdominalprojecting vagal preganglionic cell bodies are present mainly within the caudal and rostral regions of DMV (23,38,56), and microinjection of L-arginine into the DVC decreases intragastric pressure (23) via an excitatory effect on DMV neurons (46). In rodents, apelin is known to activate the L-arginine-NOS pathway in peripheral vasculature (22,57), and more importantly, recent studies have shown that central administration of apelin induces hypothalamic NO release in mice (14,16).…”
Section: Discussionmentioning
confidence: 99%
“…Aktivitas enzim NOS dijadikan dasar metode histokimia sederhana untuk menggambarkan sel yang mengandung NOS yaitu dengan pewarnaan NADPH-d (Sehirli et al, 2014;Benesova et al, 2004). Kerusakan mukosa sekum menyebabkan masuknya kalsium (Ca 2+ ) ke dalam dinding sekum, sebagai akibatnya potensial aksi dalam sel-sel ganglion mienterik meningkat.…”
Section: Hasil Dan Pembahasanunclassified